The political theology of Paul Tillich - Baard, Rachel Sophia (Faith and politics political theology in a new key, 2024)
"This volume explores the political theology of Paul Tillich, one of the foremost thinkers of the twentieth century. Tillich's discerning analysis of fascism, grounded in his socialist commitments, and continuing efforts to write theology in correlation with culture, make his voice a crucial one for contemporary political theology"--